2010
DOI: 10.3892/ijmm_00000371
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor expression in ophthalmic pterygia and normal conjunctiva

Abstract: Abstract. The expression of growth factors in ophthalmic pterygium and phenotypically normal conjunctiva was examined and correlated with the clinical findings. Fifteen specimens of ophthalmic pterygia and 8 specimens of phenotypically normal conjunctiva were examined. Total RNA was extracted from all specimens and mRNA levels for transforming growth factor (TGFB1), vascular endothelial growth factor (VEGFA), basic fibroblast growth factor (FGF2), epidermal growth factor (EGF) and insulin-like growth factor (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 16 publications
(24 reference statements)
0
27
0
Order By: Relevance
“…It can cause chronic ocular irritation, induced astigmatism, tear film disorders and descreased vision secondary to growth over the visual axis [69,70]. Although the exact etiology is unknown, the exposure to ultraviolet (UV) radiation is believed to be the main risk factor [69,70]. Age, chronic inflammation, microtrauma, and hereditary factor can contribute [70,71].…”
Section: Pterygiummentioning
confidence: 99%
See 2 more Smart Citations
“…It can cause chronic ocular irritation, induced astigmatism, tear film disorders and descreased vision secondary to growth over the visual axis [69,70]. Although the exact etiology is unknown, the exposure to ultraviolet (UV) radiation is believed to be the main risk factor [69,70]. Age, chronic inflammation, microtrauma, and hereditary factor can contribute [70,71].…”
Section: Pterygiummentioning
confidence: 99%
“…Although the exact etiology is unknown, the exposure to ultraviolet (UV) radiation is believed to be the main risk factor [69,70]. Age, chronic inflammation, microtrauma, and hereditary factor can contribute [70,71]. Studies believe that the genetic trauma mediated by UV rays could alter the expression of cytokines such as IL-6…”
Section: Pterygiummentioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards, other drugs were found to play a role in reducing the recurrence rate, which include doxorubicin and steroids, and more recently, alcohol and anti-VEGF (17,18). In the last few years, it was reported that the level of VEGF in pterygium tissue was increased compared with the levels in the normal conjunctiva, which justified the use of anti-VEGF to treat pterygium (19).…”
Section: Chemotherapymentioning
confidence: 99%
“…Pterygium is a disease characterized by surface ocular lesions associated with chronic ultraviolet exposure in which the primary effect is a solar actinic elastosis within the stroma and all other changes are secondary to the primary effect (1)(2)(3)(4)(5)(6)(7). Pterygium is characterized by cellular proliferation, inflammatory infiltration, fibrosis, angiogenesis, and extracellular matrix breakdown; the lesion begins to grow from limbal epithelium and invades the cornea centripetally followed by conjuntival epithelium, exhibiting degenerative and hyperplastic changes (1-7).…”
Section: Introductionmentioning
confidence: 99%